Socio-economic Impact Of Selected Waqf Projects: Terengganu Culinary Academy & USIM's Specialist Medical Clinic - Mohd Fazdli Rosli; Mohammad Haji Alias; Suhaila Abdul Hamid (International Research Centre of Islamic Economics, 2024)
In Malaysia, the management of waqf has been placed under the supervision/purview of State Islamic Religious Councils (SIRC). They are the sole trustees of waqf as enshrined in the Malaysian Federal Constitution/respective State’s waqf enactments. In order to ensure the betterment of the socio-economic impact to the society by employing the awqaf mechanisms, the development of waqf either the physical or non-physical development must be under the management and purview of SIRCs. Federal agencies such as Department of Awqaf, Zakat and Hajj (JAWHAR) and Malaysian Awqaf Foundation (YWM) have helped in enhancing the potential of waqf in Malaysia. Involvement of other agencies also contributed to the success story of the waqf developments in Malaysia. Thus, this paper will focus on: firstly, the basic concepts of waqf and its legislation in Malaysia and secondly the preliminary study on the socio-economic impact of selected waqf projects. The selected waqf projects are the Terengganu Culinary Academy and USIM’s Specialist Medical Clinic (USMC). The former had been developed as joint ventures between SIRC and YWM and other agencies in the areas of education/training. We will look at the mechanism of its establishment and the socio-economic impact of the development that brings fruitful benefits thereby empowering the mawquf ‘alaih (the intended beneficiaries). The USMC is a joint cooperation between USIM and the SRIC NS which committed RM 2 million (RM 1 million as waqf grant and RM 1 million as Qardhul Hasan towards establishment of the clinic. The State Government provided funds to establish a specialist mobile clinic which facilitates medical specialists from USMC to do medical screenings of patients in rural areas.